A non-cardiomyocyte autonomous mechanism of cardioprotection involving the SLO1 BK channel - Wojtovich, Andrew P.; Nadtochiy, Sergiy M.; Urciuoli, William R.; Smith, Charles O.; Grunnet, Morten; Nehrke, Keith; Brookes, Paul S. (PeerJ, 2013)
Opening of BK-type Ca2+ activated K+ channels protects the heart against ischemia-reperfusion (IR) injury. However, the location of BK channels responsible for cardioprotection is debated. Herein we confirmed that openers of the SLO1 BK channel, NS1619 and NS11021, were protective in a mouse perfused heart model of IR injury. As anticipated, deletion of the Slo1 gene blocked this protection. However, in an isolated cardiomyocyte model of IR injury, protection by NS1619 and NS11021 was insensitive to Slo1 deletion. These data suggest that protection in intact hearts occurs by a non-cardiomyocyte autonomous, SLO1-dependent, mechanism. In this regard, an in-situ assay of intrinsic cardiac neuronal function (tachycardic response to nicotine) revealed that NS1619 preserved cardiac neurons following IR injury. Furthermore, blockade of synaptic transmission by hexamethonium suppressed cardioprotection by NS1619 in intact hearts. These results suggest that opening SLO1 protects the heart during IR injury, via a mechanism that involves intrinsic cardiac neurons. Cardiac neuronal ion channels may be useful therapeutic targets for eliciting cardioprotection.
Keywords: Large conductance potassium channel; Ischemia; Reperfusion; Preconditioning; Cardiac neurons; NS1619; NS11021